Where are races won (and lost)? - Mason, B. (coachesinfo.com, 1999)
An analysis of the 1998 World Swimming Championship competition analysis data from Perth indicated that the relationship between the race performance and stroke length was not significant, apart from in the Mens 100 metre freestyle event. It was also evident that average free swimming velocity was related to the race performance for all events. This was to be expected. The race performance in the backstroke and breaststroke was related to both start and turn performance. In the butterfly events, race performance was related to turn performance. In the freestyle sprint events the start performance played a significant role whereas in the middle distance events, the turn performance was significantly related to the race performance. None of turn, finish, or start performance played a significant role in the distance freestyle events. In the individual medley events, turn performance was significantly related to race performance. The order of importance of free swimming velocity in the various strokes on race performance, with the exception of the Mens 200 metre individual medley, was in order backstroke, butterfly, breaststroke and freestyle. The above information is directly relevant to a general competition model. However, individual swimmer competition models may differ significantly from the general model. While it is important to understand the implications of the general competition model on overall performance, an individual swimmer's performance is related to: 1 The ability of the coach to determine the most effective competition model for the swimmer. 2 The coach and swimmer ensuring that appropriate training occurs to achieve the competition model. 3 Ensuring that the swimmer swims to the model in competition